Review Bentuk Integrasi Islam dalam Pendidikan IPA di Indonesia - Riza Umami; Noor Fanika; Muhamad Imaduddin (ISLAMIKA, 2021)
Research aims to determine the form of application of Islamic integration in science education in Indonesia. The method in this research uses a systematic review meta-analysis method. The data used in the study were obtained by collecting journals using the Sinta journals indeks 1 to 6. This time the writer used qualitative techniques and used the prism method. The result showed that in the jourals Sinta 1 to Sinta 6 there were 193 journals found in the search for keywords on science and science education. From 193 journals, it was found that there were 47 articles related to Islam and 10 articles related to the Al-quran. It is concluded that the application of Islamic integration in science education has been carried out quite a lot and has various forms of application of Islamic integration. Researchers found various topics related to Islamic integration. However, the integration of Islam in the form of science learning in Indonesia is still small because the number of resources with a background in humanities and social science is more dominant. The development of Islamic values in education can be done through the development model of teaching materials, methods, or learning approaches.